Spatial and Temporal Genetic Analysis of Walleyes in the Ohio River. Issue 6 (2nd November 2017) - Page, Kevin S.; Zweifel, Richard D.; Stott, Wendylee
Abstract: Previous genetic analyses have shown that Walleyes Sander vitreus in the upper Ohio River comprise two distinct genetic strains: (1) fish of Great Lakes origin that were stocked into the Ohio River basin and (2) a remnant native strain (Highlands strain). Resource agencies are developing management strategies to conserve and restore the native strain within the upper reaches of the Ohio River. Hybridization between strains has impacted the genetic integrity of the native strain. To better understand the extent and effects of hybridization on the native strain, we used mitochondrial DNA and microsatellite markers to evaluate the spatial (river sections) and temporal (pre- and poststocking) genetic diversity of Ohio River Walleyes. Contemporary Lake Erie Walleyes and archival museum specimens collected from the Ohio River basin were used for comparison to contemporary Ohio River samples. Although there was evidence of hybridization between strains, most of the genetic diversity within the Ohio River was partitioned by basin of origin (Great Lakes versus the Ohio River), with greater similarity among river sections than between strains within the same section. Results also suggested that the native strain has diverged from historical populations. Furthermore, notable decreases in measures of genetic diversity and increased relatedness among native-strain Walleyes within two sections of the Ohio River may be related to stocking aimed at restoration of the Highlands strain. Our results suggest that although the Highlands strain persists within the Ohio River, it has diverged over time, and managers should consider the potential impacts of future management practices on the genetic diversity of this native strain. Received March 17, 2017; accepted July 20, 2017Published online September 25, 2017